MENINJAU KINERJA BANK SYARIAH DI INDONESIA - Sagantha, Fitri (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
To show the role, then show the performance. Maybe, the term is right for the bank. The existence of banks influences economic stability, therefore financial performance must be good. There is no choice but to increase the entire financial ratio. Interest in reviewing the financial ratios of banks, especially Islamic banks, is the goal to be achieved in this study. Use financial statements as data, and analyze the extent of their performance and influence. For this reason, a quantitative approach and regression analysis are needed. So that research results can be explained properly. The findings in this study suggest that the performance of Islamic banks is relative. Its role is not yet at a significant stage for the economy, and it is still far from conventional banks